2020
DOI: 10.1111/gwat.12986
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Impact of a Heated Basement on Groundwater Temperatures in Bratislava, Slovakia

Abstract: Groundwater temperature is a useful hydrogeological parameter that is easy to measure and can provide much insight into groundwater flow systems, but can be difficult to interpret. For measuring temperature directly in the ground, dedicated specifically designed monitoring wells are recommended since conventional groundwater wells are not optimal for temperature monitoring. Multilevel monitoring of groundwater temperature is required to identify contributions of different possible heat inputs (sources) on meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 26 publications
(48 reference statements)
0
2
0
Order By: Relevance
“…Structures built into the ground and the associated heat flux from these are known to impact ground temperatures, with anomalous temperatures propagating particularly far through groundwater flow (Ferguson and Woodbury, 2004; Bidarmaghz et al, 2020). Such temperature anomalies can have knock-on effects, impacting cooling and heating requirements to maintain underground spaces at comfortable levels (particularly due to groundwater not transporting away as much heat (Blum et al, 2021)), groundwater quality, and the functioning of underground biospheres (Benz et al, 2015; Attard et al, 2016; Bayer et al, 2019; Krcmar et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Structures built into the ground and the associated heat flux from these are known to impact ground temperatures, with anomalous temperatures propagating particularly far through groundwater flow (Ferguson and Woodbury, 2004; Bidarmaghz et al, 2020). Such temperature anomalies can have knock-on effects, impacting cooling and heating requirements to maintain underground spaces at comfortable levels (particularly due to groundwater not transporting away as much heat (Blum et al, 2021)), groundwater quality, and the functioning of underground biospheres (Benz et al, 2015; Attard et al, 2016; Bayer et al, 2019; Krcmar et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The cumulative effect of these heat sources and sinks is a net-increase in underground temperatures, known as the Subsurface Urban Heat Island (SUHI). Increased subsurface temperatures can impact ventilation and cooling costs of underground spaces, efficiency of geo-energy systems, quality and quantity of groundwater flow, the health and maintenance of underground structures, and ecosystems [1][2][3][4][5][6][7][8][9][10], as well as goods production in underground spaces such as wine cellars [11]. It has been recommended that the use of increased shallow subsurface ground temperatures for energy generation could help mitigate negative impacts [12].…”
Section: Introductionmentioning
confidence: 99%
“…The scarcity of relevant data is an issue present in a number of studies modelling the subsurface, often resulting in the need to employ modelling sim-plifications (in combination with reducing computational complexity), such as of feature geometry (e.g. basements) or of the modelling of hydrology, to name but a few [1,9,[32][33][34][35][36][37][38][39]. In particular, one aspect that has not been subject to extensive investigation is the impact of surface elevation at city-scale modelling, as in most cases a flat surface is assumed for simplicity.…”
Section: Introductionmentioning
confidence: 99%
“…In the case of Schieks Cave, the groundwater direction in the shallow Quaternary aquifer indicates flow from the west, through the heavily commercialized Nicollet Mall and the densest skyscraper cluster, towards the cave (Kanivetsky, 1989). The source of the heat is likely due to heated buildings as was shown by Krcmar et al (2020), who reported groundwater temperatures had risen 3.2 K by flowing past a building in Bratislava, Slovakia.…”
mentioning
confidence: 96%